Towards the professional profile of the “expert” teacher. Theoretical models and methodological proposals for an epistemology of teacher professionalism in the Italian school context - Salvadori, Ilaria (Formazione & insegnamento, 2019)
Developing a professional profile of the expert teacher is a complex operation that forces us to reflect on the aims and meanings we attribute to the whole teaching and learning process. In the complexity of our reality, teachers are required to have new and specific competences, methodological knowledge and an expertise to invest both in terms of the students’ educational success and of their own professional training. The quality of the training systems is played on these two aspects, considering it through the perspective of the improvement rather than the accountability. In Italy, the legislation has tried to outline the figure of the teacher in terms of merit, but we can look for other viewpoints in the international literature on Educational Expertise and above all on Teacher Leadership. Leadership can become a tool to improve teaching processes through the dynamic training of the teacher’s identity as a marker of his expertise.